PERKEMBANGAN POLITIK DAN EKONOMI MASYARAKAT INDONESIA PADA MASA AWAL REFORMASI TAHUN 1998-1999 - Maria Winda Klaudia; Ida Bagus Nyoman Wartha (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
Based on the description above, the research problem is focused on 1) How is indonesian’s situation ahead of the reformation? 2) How was indonesian’s political and economic reform period 1998-1999? 3) How was indonesian’s political and economic development in the early years of 1998-1999? The method used in this study is the historical method. Data collection techniques using observation and documentation techniques,while the data analysis techniques used are qualititative descriptive. The results of the study showed that political and economic development gave good influence, especially in the political field, the antusiasm and participation of the people in the political field were increasingly high, one of them was the formation of new parties. There is an improvement in human right (HAM) which was previously violated during the new order era, justice in the whole word. While in the economic field to improve the economic which was slumped mainly in the bangking sector, the goverment formed the national bangking restructuring agency (BPPN). Furthermore the govermet issued no 5 of 1999 concering the prohibition of monopolistic pratices and unfair competition, as well as law no 8 of 1999 concering consumer protection. The conclusions of the political and economic development of Indonesians society in the early days of reform led to better changes, especially government policies which gave wider room for rights to express opinions and thughts both oral and written. Whereas in the economic field the rate of economic growth began to be positive although not far from 1%.